2019
DOI: 10.7717/peerj.6422
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of OsFTL10 induces early flowering and improves drought tolerance in Oryza sativa L.

Abstract: Flowering time control is critically important for the reproductive accomplishment of higher plants as floral transition can be affected by both environmental and endogenous signals. Flowering Locus T-like (FTL) genes are major genetic determinants of flowering in plants. In rice, 13 OsFTL genes have been annotated in the genome and amongst them, Hd3a (OsFTL2) and RFT1 (OsFTL3) have been studied extensively and their functions are confirmed as central florigens that control rice flowering under short day and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 44 publications
2
27
0
Order By: Relevance
“…The FT gene encodes a long-distance mobile signaling protein called "florigen", which plays a central role in flowering regulation [3,7,8]. This gene belongs to the phosphatidylethanolamine-binding protein (PEBP) gene family, which exists in all kingdoms of life [9].…”
Section: Introductionmentioning
confidence: 99%
“…The FT gene encodes a long-distance mobile signaling protein called "florigen", which plays a central role in flowering regulation [3,7,8]. This gene belongs to the phosphatidylethanolamine-binding protein (PEBP) gene family, which exists in all kingdoms of life [9].…”
Section: Introductionmentioning
confidence: 99%
“…In agricultural production, premature senescence of leaves shortens the functional period of leaves and thus reduces the rice yield. The FTL10 is an early flowering line by overexpressing the OsFTL10 gene (Fang et al 2019). The expression level of OsFTL10 gene in FTL10 was significantly higher than that in the wild type.…”
Section: Discussionmentioning
confidence: 99%
“…Plant material: Oryza sativa L. cv. Zhonghua 11 (ZH-11), and an early flowering mutant FTL10 were used in this study (Fang et al 2019). The pasteurized seeds were planted in an artificial climate incubator and grown under controlled conditions with an average temperature of 33°C light/28°C dark, air humidity of 80%, and a photoperiod of 14 h light/10 h dark [PAR of 100 μmol(photon) m -2 s -1 ].…”
Section: Methodsmentioning
confidence: 99%
“…Still, it has been proposed that DE can be used to obtain quick-growing, early-flowering cereal varieties, which would be especially useful in temperate regions like the Mediterranean area where terminal drought is expected to affect plants toward the end of the crop season (Shavrukov et al, 2017). Furthermore, it has been recently shown that OsFTL10, one of the 13 FLOWERING LOCUS T-LIKE (FTL) genes annotated in the rice genome, is induced by both drought stress and GA, and when overexpressed in transgenic rice plants confers early flowering and improves drought tolerance (Fang et al, 2019). However, as these transgenic rice lines were not tested in a field trial, it is unknown whether engineering FTL genes could deliver cereal varieties with superior drought performances and good yield in both dry and well-watered conditions.…”
Section: Major Traits Contributing To Drought Resistance Early Flowermentioning
confidence: 99%